Cas12a-Based On-Site and Rapid Nucleic Acid Detection of African Swine Fever - Bai, Jing; Lin, Haosi; Li, Haojian; Zhou, Yang; Liu, Junshan; Zhong, Guorui; Wu, Luting; Jiang, Weifan; Du, Hongli; Yang, Jinyi; Xie, Qingmei; Huang, Lizhen (Frontiers in Microbiology, 2019)
The mortality rate of hemorrhagic African swine fever (ASF), which targets domestic pigs and wild boars is caused by African swine fever virus (ASFV), can reach 100%. Since the first confirmed ASF outbreak in China on 3 August 2018, 156 ASF outbreaks were detected in 32 provinces. About 1,170,000 pigs were culled in order to halt further spread. There is no effective treatment or vaccine for it and the present molecular diagnosis technologies have trade-offs in sensitivity, specificity, cost and speed, and none of them cater perfectly to ASF control. Thus, a technology that overcomes the need for laboratory facilities, is relatively low cost, and rapidly and sensitively detects ASFV would be highly valuable. Here, we describe an RAA-Cas12a-based system that combines recombinase-aided amplification (RAA) and CRISPR/Cas12a for ASFV detection. The fluorescence intensity readout of this system detected ASFV p72 gene levels as low as 10 aM. For on-site ASFV detection, lateral-flow strip readout was introduced for the first time in the RAA-Cas12a based system (named CORDS, Cas12a-based On-site and Rapid Detection System). We used CORDS to detect target DNA highly specifically using the lateral-flow strip readout and the assay displayed no cross-reactivity to other 13 swine viruses including classical swine fever. CORDS could identify the ASFV DNA target at femtomolar sensitivity in an hour at 37 °C, and only requires an incubator. For ease of use, the reagents of CORDS were lyophilized to three tubes and remained the same sensitivity when stored at 4 °C for at least 7 days. Thus, CORDS provide a rapid, sensitive and easily operable method for ASFV on-site detection. Lyophilized CORDS can withstand long-term transportation and storage, and is ready for field-based applications.